Stay-at-home, Safe at Home? A survey of parental home safety practices before and during the COVID-19 pandemic - Kristin J. Roberts; Rebecca J. McAdams; Lara B. McKenzie (BMC, 2022)
Abstract Background To slow the spread of COVID-19, many nonessential businesses, daycares, and schools closed, and areas imposed "stay-at-home" orders. Closures led to young children spending more time at home, traditionally, the place where more than one-half of unintentional pediatric injuries occur. The objective of the current study was to describe parental safety perceptions and confidence, safety device purchase and installation, and injury prevention practices and behaviors, in homes with children 6 years of age and younger, before and during the COVID-19 pandemic. Methods A cross-sectional survey with a convenience sample of US participants, 18 years or older, was conducted from November 2020 to February 2021. Parents of children (≤ 6 years) were recruited via social media ads and posts on Facebook and Twitter and invited to complete an anonymous, online survey about their home safety practices before and during the COVID-19 stay-at-home order. Upon completion, parents could participate in a prize drawing to receive one of five $100 gift cards. Results A total of 499 participants completed the survey. Most (47.9%) were 45-54 years of age and reported the amount of time at home increased for them (93.9%) and their children (90.6%) during the stay-at-home period. Thirty-seven percent (36.9%) of parents considered their homes safe but recognized room for improvement and felt confident in their ability to make their homes safe for their children (72.8%). From the time before until the COVID-19 stay-at-home orders were in place, parents increased their home injury prevention practices (42.3%). Parents that had identified unsafe areas in the home before the stay-at-home order were significantly more likely to increase their safety behaviors, take childproofing actions, and purchase or install safety devices during the stay-at-home order (p < 0.0001). Parents with younger children (5 years) were significantly more likely than parents with older children to take childproofing actions (p < .0001) including purchasing and installing safety devices (p < 0.0001). Conclusions Spending more time at home during the COVID-19 pandemic may have helped the sampled parents, especially those with younger children, identify unsafe areas in their homes and encourage them to modify their behaviors, and purchase and install safety devices to help make their homes safer for their children.